The effectiveness of community-wide screening for pulmonary tuberculosis: a systematic review - Susanna S. van Wyk; Ntombifuthi Blose; Lester Kapanda-Phiri; Mareli Claassens; Taryn Young (EClinicalMedicine)
Summary: This systematic review evaluated the effectiveness of community-wide screening for pulmonary tuberculosis (TB) in high-burden areas by analysing randomised controlled trials (RCTs). The review focused on interventions offering TB screening to entire communities, comparing them to standard care or alternative approaches. The main outcome assessed was microbiologically confirmed TB diagnoses, including rates and prevalence. We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, WHO Global Index Medicus, Web of Science, and trial registries up to 27 May 2024, without language restrictions. Screening, data extraction, and risk of bias assessment were done in duplicate. Results were not pooled. Certainty of the evidence was assessed using GRADE. PROSPERO: CRD42023453356. We included six cluster-RCTs after screening 2460 titles/abstracts and 86 full-text articles. The evidence for symptom screening was very uncertain. We found that sputum smear microscopy screening may result in little to no difference in the prevalence of culture-confirmed TB (n = 962,655, RR 1.09; 95% CI: 0.86–1.38, 1 RCT, low certainty evidence). Community-wide nucleic acid amplification test (NAAT) screening probably reduces the prevalence of NAAT-positive TB (n = 105,108, RR 0.56; 95% CI: 0.40–0.78, 1 RCT, moderate certainty evidence). Community-wide screening for pulmonary TB may reduce TB prevalence if done annually with an accurate screening test and high coverage.